Sex differences in copper concentrations during a sports season in soccer players - Toro-Román, V.; Munoz; Muñoz, D.; Maynar-Marino, M.; Clemente-Gil, S.; Robles-Gil M. C. (Nutrients, 2023)
Physical training produces changes in the concentrations of trace mineral elements. Sex differences in copper (Cu) concentrations in athletes are scarce. The objectives of this study were (i) to analyze changes in intracellular (erythrocytes and platelets) and extracellular (plasma and urine) Cu concentrations during a sports season in soccer players and (ii) to analyze sex differences. A total of 46 soccer players (22 men and 24 women) participated in the study. Three assessments were performed throughout the sports season. Anthropometry, body composition, nutritional intake, physical condition, female hormones (menstrual cycle) and hematology were evaluated, as well as Cu determination (plasma, urine, erythrocytes, and platelets). Regarding longitudinal differences, there were discrepancies in plasma, urine, absolute erythrocyte, and absolute platelet Cu concentrations (p < 0.05). There were differences between sexes in Cu concentrations in urine, erythrocytes relative to cell number and in platelets relative to cell number (p < 0.05). During a sports season, there are changes in Cu concentrations in soccer players. Likewise, there could be sex differences in urinary, erythrocyte and platelet Cu concentrations.